Odpowiedzi

Najlepsza Odpowiedź!
2010-01-09T14:03:38+01:00
A) 3x -4y =6
2x + 2y = 6 /*(-2)

3x -4y =6
-4x -4y = -12

-x = -6 / : (-1)
x = 6

x= 6
2*6 + 2y = 6

x=6
2y = -6 /2

x=6
y= -3

b) - 5x - y = -3 / *2
-2x +2y = -6

-10x -2y = -6
-2x +2y = -6

-12x = -12 / : (-12)
x = 1

x=1
- 5*1 - y = -3

x=1
-y = 2 /:(-1)

x=1
y = -2

c) -x -5y =0
-5x -y = 0 /* (-5)

-x -5y =0
25x + 5y = 0

24x = 0 / :24
x= 0

x=0
-0 -5y =0

x=0
-5y=0

x=0
y=0<ale nie wiem czy to jest dobrze>

d) 3/4 x - 2/3y = 2
1/4x + 2/3y = 6

9/12x - 8/12y = 2 / *12
3/12x + 8/12y = 6/ *12

9x -8y = 24
3x + 8y = 72 / *(-1)

9x -8y = 24
-3x - 8y = -72

6x = -48 / :6
x = -8

x=-8
9* (-8) -8y = 24

x=-8
-8y = 96/ (-8)

x= -8
y= -12